Bringing the Boss’s Politics In: Supervisor Political Ideology and the Gender Gap in Earnings - Briscoe, Forrest; Joshi, Aparna (Academy of Management Journal, 2017)
The gender gap in earnings and rewards remains persistent across many professional and managerial work contexts. In these settings, where there are few objective criteria for performance and organizational mechanisms are weak, we propose that personal political values can serve as a powerful influence on whether supervisors reduce or enhance inequalities in performance-based rewards. We develop theory about how political liberalism versus conservatism affects supervisors’ perceptions and allocative decision-making. Combining internal personnel and billings data with publicly available political donation records in a large law firm, we test the effect of political ideology among supervising law firm partners on the performance-based bonuses awarded to male and female subordinate lawyers. We find the male–female gender gap in performance-based pay is reduced for professional workers tied to liberal supervisors, relative to conservative supervisors. We further find this political ideology effect increases for workers with greater seniority in the organization. Our findings contribute to an understanding of the determinants of the gender earnings gap, suggesting that, in settings where managers have leeway over rewards and careers, their personal political beliefs have an important influence on outcomes for male and female workers.